Self-care guidelines for patients in the post-hematopoietic stem cell transplantation period: a scoping review - Anália Andréia de Araújo Nascimento; Jéssica Cristina Alves de Melo; Katiane Domingos Soares; Anne Caroline Lisboa Marinho; Sara Eloise Argimiro Ribeiro; Isabelle Campos de Azevedo (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To map the evidence on self-care guidelines for patients in the post-hematopoietic stem cell transplantation (HSCT) period. Method: Scoping review supported by Joanna Briggs Institute recommendations, with searches conducted between March and April 2022 in national and international databases and repositories of theses and dissertations. Results: Of the 11 studies that composed the final sample, the guidelines had a social and personal aspect, as post-transplant patients need to follow numerous essential recommendations for the prevention of infections and complications for successful treatment and improved quality of life. Conclusion: Knowing the self-care guidelines that must be performed by post-HSCT patients is fundamental for the nursing team to provide the necessary information for care outside the controlled environment of the hospital, in addition to minimizing episodes of infection, death, and increasing the survival and quality of life of transplant recipients.